CRISPR-Cas9 Mediated RNase L Knockout Regulates Cellular Function of PK-15 Cells and Increases PRV Replication - Sui, Chao (Biomed Res Int, 2019)
Ribonuclease L (RNase L) is an important antiviral endoribonuclease regulated by type I IFN. RNase L is activated by viral infection and dsRNA. Because the role of swine RNase L (sRNase L) is not fully understood, in this study, we generated a sRNase L knockout PK-15 (KO-PK) cell line through the CRISPR/Cas9 gene editing system to evaluate the function of sRNase L. After transfection with CRISPR-Cas9 followed by selection using puromycin, sRNase L knockout in PK-15 cells was further validated by agarose gel electrophoresis, DNA sequencing, and Western blotting. The sRNase L KO-PK cells failed to trigger RNA degradation and induced less apoptosis than the parental PK-15 cells after transfected with poly (I: C). Furthermore, the levels of ISGs mRNA in sRNase L KO-PK cells were higher than those in the parental PK-15 cells after treated with poly (I: C). Finally, both wild type and attenuated pseudorabies viruses (PRV) replicated more efficiently in sRNase L KO-PK cells than the parental PK-15 cells. Taken together, these findings suggest that sRNase L has multiple biological functions including cellular single-stranded RNA degradation, induction of apoptosis, downregulation of transcript levels of ISGs, and antiviral activity against PRV. The sRNase L KO-PK cell line will be a valuable tool for studying functions of sRNase L as well as for producing PRV attenuated vaccine.